Development of effective sequence multi-barrier for nitrate remediation in groundwater system: Geochemical and analytical approaches / Muntaka Dahiru - Muntaka , Dahiru (2019)
Denitrification is a natural process of remediation, often exploited with modification to treat nitrate-polluted water in subsurface region. Carbon rich materials have been employed as electron donors in permeable reactive barriers (PRB), but their early depletion present serious challenge to the remediation technology. To find solution to these challenges, this study was conducted as a preliminary screening and selection of carbon sources for usage in simulated sequence multi barrier reactive media column. The study proposes and test a novel composition and effective packing structure of gate materials using wood chips, date seed, Moringa oleifera, sawdust, and paleo beach soil for denitrification. Our experimental findings lead to a series of trials in optimization for efficiency tests, which were followed by the addition of CaCO3 to buffer medium and enhance the much-desired complete denitrification process. The results obtained from the field (Bachok) suggests multiple redox activity and simultaneous occurrences of heterotrophic and autotrophic denitrification at different soil strata. Evaluation of general variation pattern across the selected area in Kelantan revealed that the principle component analysis (PCA), hierarchical cluster analysis (HCA) and linear discriminant analysis (LDA) apportioned three parameters (SO42, Cl and conductivity) to the coastal sites and two parameters (Fe in the presence of NH4+ or Fe in the presence of NO3) to in-land sites. The packing structure of the proposed sequence multi-barrier has dominant composition of date seed, wood chips, Moringa oleifera seed and activated carbon in the 1st, 2nd, 3rd and 4th compartments, respectively. The efficiency of the column setup was found to be dependent upon the ratio of the constituents, composition of the materials and the initial concentration of NO3 in the influent. The system shows removal efficiency of 96.4% and 98% of nitrite NO2 and NO3 and the attenuation of organic by-products (determined as total organic carbon) reached 53% within the first 46 cm height of the soil column. Surface characterization techniques of FESEM-EDX on the date seed and wood chips revealed a wider perforation in wood chips than in date seed, indicating preferential consumption of wood chips over date seed. Moreover, the results obtained from mesh bag technique revealed that the rate of decomposition within the date seed partitioning (endosperm and mannan-rich cell wall) and between date seed and wood chips differs with significant values, pointing to preferential consumption of one carbon source over the other and hence, fulfilling the need for delayed decomposition to ensure longer life span. It is also evident from the EDX that 30% reduction of carbon in wood chips is by far more than the 8.75% reduction of carbon in date seed for the same period. FTIR spectra revealed active redox conditions consisting of bond breakages/formation and addition and subtraction of functional groups that indicates more of oxidation process during decomposition. In summary, the process of decomposition entails multiple redox conditions at different site, depending on carbon of functional group, which is utilized by the bacteria.